Translation and State The Mahābhārata at the Mughal Court - Willis, Michael (Beyond Boundaries, 2022)
In 1587, Abū al-Faz̤l ibn Mubārak - a favourite at the Mughal court and author of the Akbarnāmah - completed his Preface to the Persian translation of the Mahābhārata. This book is the first detailed study of Abū al-Faz̤l's Preface. It offers insights into manuscript practices at the Mughal court, the role a Persian version of the Mahābhārata was meant to play, and the religious interactions that characterised 16th-century India.